Calreticulin exposure by malignant blasts correlates with robust anticancer immunity and improved clinical outcome in AML patients - Fucikova, Jitka; Truxova, Iva; Hensler, Michal; Becht, Etienne; Kasikova, Lenka; Moserova, Irena; Vosahlikova, Sarka; Klouckova, Jana; Church, Sarah E; Cremer, Isabelle; Kepp, Oliver; Kroemer, Guido; et al. (Blood, 2016)
Cancer cell death can be perceived as immunogenic by the host only when malignant cells emit immunostimulatory signals (so-called "damage-associated molecular patterns," DAMPs), as they die in the context of failing adaptive responses to stress. Accumulating preclinical and clinical evidence indicates that the capacity of immunogenic cell death to (re-)activate an anticancer immune response is key to the success of various chemo- and radiotherapeutic regimens. Malignant blasts from patients with acute myeloid leukemia (AML) exposed multiple DAMPs, including calreticulin (CRT), heat-shock protein 70 (HSP70), and HSP90 on their plasma membrane irrespective of treatment. In these patients, high levels of surface-exposed CRT correlated with an increased proportion of natural killer cells and effector memory CD4(+) and CD8(+) T cells in the periphery. Moreover, CRT exposure on the plasma membrane of malignant blasts positively correlated with the frequency of circulating T cells specific for leukemia-associated antigens, indicating that ecto-CRT favors the initiation of anticancer immunity in patients with AML. Finally, although the levels of ecto-HSP70, ecto-HSP90, and ecto-CRT were all associated with improved relapse-free survival, only CRT exposure significantly correlated with superior overall survival. Thus, CRT exposure represents a novel powerful prognostic biomarker for patients with AML, reflecting the activation of a clinically relevant AML-specific immune response.
Keywords: genetická transkripce; Leukemia, Myeloid, Acute; Th1 buňky; Calreticulin; proporcionální rizikové modely; Humans; proteiny tepelného šoku HSP90; alarminy; lidé středního věku; Proportional Hazards Models; Multivariate Analysis; Transcription, Genetic; Immunity; Female; buněčná smrt; Phenotype; výsledek terapie; lidé; CD8-Positive T-Lymphocytes; imunita; CD8-pozitivní T-lymfocyty; Alarmins; HSP90 Heat-Shock Proteins; ženské pohlaví; multivariační analýza; Male; Blast Crisis; Middle Aged; fenotyp; Treatment Outcome; regulace genové exprese u leukemie; stanovení celkové genové exprese; proteiny tepelného šoku HSP70; Th1 Cells; kalretikulin; blastická krize; Gene Expression Profiling; mužské pohlaví; Cell Death; akutní myeloidní leukemie; HSP70 Heat-Shock Proteins; Gene Expression Regulation, Leukemic